Oligomerization of the Nrdp1 E3 Ubiquitin Ligase Is Necessary for Efficient Autoubiquitination but Not ErbB3 Ubiquitination - Printsev, Ignat (American Society for Biochemistry and Molecular Biology, 2014)
Overexpression of the ErbB3 receptor tyrosine kinase protein in breast and other cancers contributes to tumor malignancy and therapeutic resistance. The RBCC/TRIM family RING finger E3 ubiquitin ligase Nrdp1 mediates the ubiquitination of ErbB3 in normal mammary epithelial cells to facilitate receptor degradation and suppress steady-state receptor levels. Post-transcriptional loss of Nrdp1 in patient breast tumors allows ErbB3 overexpression and receptor contribution to tumor progression, and elevated lability through autoubiquitination contributes to the observed loss of Nrdp1 in tumors relative to normal tissue. To begin to understand the mechanisms underlying Nrdp1 protein self-regulation through lability, we investigated the structural determinants required for efficient autoubiquitination and ErbB3 ubiquitination. Using mutagenesis, chemical cross-linking, size exclusion chromatography, and native polyacrylamide gel electrophoresis, we demonstrate that Nrdp1 self-associates into a stable oligomeric complex in cells. Deletion of its coiled-coil domain abrogates oligomerization but does not affect Nrdp1-mediated ErbB3 ubiquitination or degradation. On the other hand, the presence of the coiled-coil domain is necessary for efficient Nrdp1 autoubiquitination via a trans mechanism, indicating that Nrdp1 ubiquitination of its various targets is functionally separable. Finally, a GFP fusion of the coiled-coil domain stabilizes Nrdp1 and potentiates ErbB3 ubiquitination and degradation. These observations point to a model whereby the coiled-coil domain plays a key role in regulating Nrdp1 lability by promoting its assembly into an oligomeric complex, and raise the possibility that inhibition of ligase oligomerization via its coiled-coil domain could be of therapeutic benefit to breast cancer patients by restoring Nrdp1 protein.